1988
DOI: 10.1071/ar9881039
|View full text |Cite
|
Sign up to set email alerts
|

Identification, distribution and population variability of great brome (Bromus diandrus Roth) and rigid brome (Bromus rigidus Roth)

Abstract: Seventeen populations of Bromus spp. were sampled from across southern Australia and accessions in the state herbaria of Western and South Australia were examined. Rigid brome (B. rigudus) differed from great brome (B. diandrus) in having shorter, sparser hairs on leaf laminae, more compact and erect panicles with shorter spikelet branches. In rigid brome, the abscission scars on the rachillae were elliptical and the lemma calluses were elongated (> 1 mm), while in great brome, these characters were circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 0 publications
1
27
1
1
Order By: Relevance
“…). These results contradict previous works in which the highest emergences and densities of B. diandrus were observed in NT compared with other soil tillage systems (Gill & Blacklow, ; Kon & Blacklow, ; Riba & Recasens, ; Kleemann & Gill, ). Higher infestation levels were found in tillage systems in which seeds are superficially buried in the soil (ChP and SS) than in MbP and NT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…). These results contradict previous works in which the highest emergences and densities of B. diandrus were observed in NT compared with other soil tillage systems (Gill & Blacklow, ; Kon & Blacklow, ; Riba & Recasens, ; Kleemann & Gill, ). Higher infestation levels were found in tillage systems in which seeds are superficially buried in the soil (ChP and SS) than in MbP and NT.…”
Section: Discussioncontrasting
confidence: 99%
“…Kon and Blacklow () noted that there is a high heritable variation within Australian populations of B. diandrus that would allow further adaptations to changing environments. Kleemann and Gill () also observed great differences in germination patterns between B. diandrus populations and noted a possible interaction between seed dormancy and crop management practices.…”
Section: Discussionmentioning
confidence: 99%
“…They are predominantly self-fertilizing annual grasses, widely distributed in Europe, Mediterranean countries and SW Asia (Smith, 1980 [31] , 1985 [32] ; Sales, 1993 [26] , 1994 [27] ). Bromus diandrus and B. rigidus have been reported as polyploids with different intraspecific ploidy levels: B. diandrus (2n = 28, 42, 56) B. rigi-dus (2n = 28, 42, 56, 70) (Devesa et al, 1990 a [2] ; Kon and Blacklow, 1988 [14] ; Sanchez Anta et al, 1986 [28] ). Bromus sterilis is a closely related diploid (2n = 14) species (Devesa et al, 1990 b [3] ; Sanchez Anta et al, 1988 [29] ; Kozuharov et al, 1981 [15] ) which was shown to be a putative genome donor for the B. diandrus±rigidus polyploid complex in our previous isozyme study (Oja and Jaaska, 1996 [22] ).…”
Section: Introductionmentioning
confidence: 99%
“…Genea, except the diploid B. fasciculatus C. Presl, are widely introduced in North and South America, Australia, and New Zealand (Mack 1981;Upadhyaya et al 1986). Some species, e.g., B. diandrus Roth, B. rigidus Roth, and B. tectorum L., have spread rapidly in new areas and become problematic weeds (Kon and Blacklow 1988;DiTomaso 2000;Novak and Mack 2001).…”
Section: Introductionmentioning
confidence: 99%